THEORETICAL ASPECTS OF THE BANKING SERVICES MARKET IN MODERN CONDITIONS - Nozimov Eldor Anvarovich (Scholar Express Journals, 2022)
This article discusses the theoretical foundations of banking services and analyzes banking services and operations. The article develops scientific and practical recommendations based on analysis.
Keywords: commercial banks; banking services; operations; payments